World religions and norms of war. - Popovski, Vesselin; Reichberg, Gregory; Turner, Nicholas (Tokyo United Nations University Press, 2009)
Over more than two millennia, the world's leading religious traditions have provided the guidance in questions of when war can be justified, and of what methods and targets are permissible in war. Linking deep historical analysis to contemporary issues, this volume provides insight to the understanding of the role and influence of religion in the state politics. The book examines the norms of war in Hinduism, in Theravada Buddhism, in Japanese religion, in Judaism, in Roman Catholic Christianity, in Eastern Orthodox Christianity, in Protestant Christianity, in Shia Islam and in Sunni Islam, and discusses norms of war in cross-religious perspective.--Publisher's description.
Introduction / Vesselin Popovski -- Religion and war / Vesselin Popovski -- Norms of war in Hinduism / Kaushik Roy -- Norms of war in Theravada Buddhism / Mahinda Deegalle -- Norms of war in Japanese religion / Robert Kisala -- Norms of war in Judaism / Jack Bemporad -- Norms of war in Roman Catholic Christianity / Gregory M. Reichberg -- Norms of war in Eastern Orthodox Christianity / Yuri Stoyanov -- Norms of war in Protestant Christianity / Valerie Ona Morkevicius -- Norms of war in Shia Islam / Davood Feirahi -- Norms of war in Sunni Islam / Amira Sonbol -- Norms of war in cross-religious perspective / Gregory M. Reichberg, Nicholas Turner and Veselin Popovski.
Keywords: Religions; War -- Religious aspects